(untitled) (Journal of humanities and social sciences exploratio, 2026)
As a representative short political satire by Kukrit Pramoj, A Country Bumpkin Visits Bangkok depicts the experiences of a peasant from a rural province, referred to as a “country bumpkin”, during his stay in Bangkok. It profoundly reveals the dark political environment and severe urban-rural dualistic contradiction in Thailand during a period of turmoil and transformation. With incisive writing, the work exposes the deception and exploitation of the grassroots people by politicians and interest groups, and truthfully reconstructs the images of marginalized citizens in Thailand’s democratic process and self-serving officials. This paper systematically explores the novel from the dimensions of character images, descriptive techniques, literary characteristics and social influence, so as to clarify its outstanding value in the history of modern and contemporary Thai literature and its far-reaching enlightenment for contemporary political system reform.